The Influence of Gender, Religiosity, and Intellectual Intelligence on Ethical Perceptions of Accounting Students with Love of Money on Ethical Perceptions of Accounting Students - Dwi Afifatul Riszqiya; Eny Maryanti (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine whether gender, religiosity, and intellectual intelligence have an influence on ethical perceptions of accounting students through love of money as an intervening variable at Muhammadiyah University of Sidoarjo and STIE Perbanas Surabaya. This type of research is quantitative, and obtained a sample of 90 respondents. The test tool uses smartPLS 3.0. The results of the study are: there is no effect of gender on ethical perceptions, religiosity has no effect on ethical perceptions, intellectual intelligence has an influence but is negative on ethical perceptions, gender has no influence on love of money, religiosity, intellectual intelligence has an influence on love of money, love of money has a negative influence on ethical perceptions, love of money has not been able to intervene for gender, religiosity, and intellectual intelligence with ethical perceptions.